Un modelo para definir la frecuencia operativa del riego para obtener máxima producción de los cultivos - Millar, Agustín A; Choudhury, Eliane N (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
A model to define operational frequency for maximum yield of crops is described. Plant response to soil moisture conditions, soil water retention and transmission characteristics, evapotranspiration and atmospheric demand are the basic information used in the model. Results of the application of the model for tomatoes, and beans in a sandy loam soil are presented. The use of world data of the yield-water relationship is discussed.